Differential evolution optimization for constrained routing in Wireless Mesh Networks - Sanni, Mistura Laide; Hassan Abdalla Hashim, Aisha; Hassan, Wan Haslina; Ahmed, Gharib Subhi Mahmoud; Anwar, Farhat; Zakaria, Omar (IEEE, 2014)
An important consideration in efficient routing design is the nature of access network and application requirements. Consequently, routing algorithm designed for general mobile ad hoc networks may not be adequate for Wireless Mesh Networks (WMN) deployment because of significant architectural differences. Furthermore, recent Internet traffic dominated by video data transmission in real-time requires path selection metrics for handling delay stringent nature of such traffic. Incidentally, the mandatory protocol defined for IEEE802.11s WMN implements layer 2 routing based in part on AODV; and even AODV expends enormous route processing on route discovery and maintenance for mobile routing nodes; which constitute overheads in WMN because of its static routing nodes in a rather stable topology with major traffic directed to and from Internet gateway. Thus this paper studies multiple constraints routing problem for path cost minimization over WMN. However, this problem is NP-complete, hence, this paper proposes fast convergent Differential Evolution metaheuristic algorithm with bandwidth and delay constraints for minimum routing cost. This solution addresses efficient and optimal routing path construction for cost and quality metrics of the application. Simulation on NS2 proves its performance advantages over AODV protocol.